USE OF COMPUTER TECHNOLOGIES IN THE EDUCATIONAL PROCESS OF TEACHING THE DISCIPLINE "INFECTIOUS DISEASES AND PHTISIATRY" - Давиденко, О.M.; Мироник, О.В. (SWorldJournal, 2022)
The use of modern medical computer technologies in the professional activities of future specialists affects the quality of the diagnostic and treatment process and the health of the nation in our country. The use of computer technology in educational wo